PENGARUH GOOD GOVERNANCE, PENGELOLAAN KEUANGAN DAERAH DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KINERJA PEMERINTAH DAERAH (STUDI EMPIRIS PADA PEMERINTAH KOTA DUMAI) - Jayanti, Yuliana Dwi; -, Yusralaini; -, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect caused by the variable good governance, financial management area and financial accounting system area of local government performance of local government in Dumai. This study uses a purposive sampling method with 70 respondents. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 17 for windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on the local governmen performancet. Partial regression test (t test) showed that the variables good governance and financial accounting system area partially affect the variable local government performance, while the partial financial management area variables do not affect the variables local government performance. The magnitude of the effect caused by Adjusted R by three variables together against the dependent variable is 28,8%, while the remaining 71,2% is influenced by other variables not examined in this study.Keywords: good governance, financial management area, financial accounting system area, local government performance, and local government in Dumai